Postsecondary Education Experience for Students with Developmental Disabilities: A Look into Perceptions of Parents of Senior High Transition Students on a Small University Campus - Friesland, Neil; King, Brad (Journal of the American Academy of Special Education Professionals, 2012)
The transition program in this study is associated with a local school district, and is currently housed on the campus of a small college in the Midwest. This transition program is for students who have been diagnosed with intellectual disabilities. The purpose of this paper is to provide information about the perceptions of parents who have or have had students in the transition program in relation to the university community and their students’ time here on the university campus. This paper also intends to educate the parents of these transition students, the university community, and the local school district about the role the university plays in relation to the campus program and its efficacy. Lastly this paper explores the possibility of, and interest in, beginning a college-level program at the university for students diagnosed with intellectual disabilities; this would allow them to earn a college certificate or an Associate’s degree.